Dulaglutide improves glucocorticoid-induced hyperglycemia in inpatient care and reduces dose and injection frequency of insulin - Hiroyuki Uchinuma; Masashi Ichijo; Noriyuki Harima; Kyoichiro Tsuchiya (BMC Endocrine Disorders, 2020)
Abstract Background Glucocorticoid (GC)-induced hyperglycemia is characterized by elevated postprandial blood glucose, which commonly requires multiple insulin injections. We investigated whether a long-acting glucagon-like peptide-1 receptor agonist, dulaglutide (Dula), safely improved GC-induced hyperglycemia in inpatients, to reduce insulin injection frequency. Methods The data of hospitalized patients with GC-induced hyperglycemia treated with Dula (Dula group, n = 38) or without (non-Dula group, n = 38) were retrospectively evaluated. Baseline data were collected at the beginning of GC treatment. The primary outcome in this study was glycemic control, which was compared between the groups using the six-point blood glucose (before and 2 h after each meal) profiles at discharge. The daily injection frequency of injectable drugs at discharge were also compared between groups. Results No specific trend of underlying diseases was observed between the non-Dula and Dula groups. The proportion of patients previously administered with GC pulse therapy was comparable between the two groups. No significant differences were observed between groups, in the starting maintenance GC dose, GC dose at pretreatment of Dula and discharge, and cumulative GC dose during the observation. Six-point blood glucose levels at pretreatment and discharge were comparable between the two groups. However, daily injection frequency of injectable drugs and insulin dose were significantly lower in the Dula group than that in the non-Dula group. No differences were observed in the number of hypoglycemic events, the elevation of serum pancreatic enzyme levels, or gastrointestinal adverse events. Conclusion These findings suggest that Dula could provide glycemic control while reducing the insulin dose and injection frequency in inpatients with GC-induced hyperglycemia. The occurrence of adverse events such as gastrointestinal symptoms and hypoglycemia did not increase in the Dula-treated patients compared to those not treated, suggesting its safety.